Corporate Governance: Can Creditors Fit in with Companies’ Board of Directors? (Malaysian Management Journal, 2010)
How do suppliers of finance make sure that firm managers enforce credit contracts, or do not invest in bad projects? This approach is missing in corporate governance research. To bridge the gap, we take steps towards developing a stakeholder perspective with the focus on examining the effects of creditor participation in a firm’s top decisions, in relation to board performance. Based on a sample of 154 questionnaire survey responses from Nigerian public firms, after relating all measured items to every construct in the statistical tests of exploratory factor analysis (EFA), we employed the use of confirmatory factor analysis (CFA) in a structural equation modelling (SEM) approach for an in-depth analysis to estimate how well the stakeholder model fits the data. Building upon the construct creditor participation, and based on the proposed theory, we confirmed three dimensions – protect risk projects, protect collateral, and enforce contracts – to be confirmed measures of the latent construct. Significant creditors such as banks interfering in the firm’s board, especially in major board decisions, can reduce the potentials of managers to engage in high-risk projects. This has significant positive effects on the board’s role performance. However, items in the two dimensions – protect collateral and enforce credit contracts show weak measurements after EFA. The consequences are a new research agenda for boards has been set. The agenda will focus on the suppliers of debt finance, as significant to the firms akin with their equity shareholders’ counterparts. This will create knowledge; reduce conflicts of interests, and exploitation; and ensure equitable distribution of firm value. The approach exposes firms to access more inclusive strategic inputs especially on important and less risky projects that will yield better margin and sustainable growth. This may stimulate further debates on other stakeholder researches that are vital to debt financiers and boards, thus becoming actionable for practitioners in decisions on projects.